KOMUNIKASI INTERPERSONAL MASYARAKAT NAGARI SALIMPAUNG DALAM MEMAHAMI COVID-19 - Ramona Putra; Ali Nupiah (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2023)
The main problem in the research on Interpersonal Communication of the Nagari Salimpaung Community in understanding Covid-19. The objectives of this research are: 1) What is the form of communication used by the Salimpaung Community to understand information about Covid-19, 2) to find out the forms and barriers of communication for the Salimpaung Community in understanding information about Covid-19. This research uses field research with a qualitative approach. The author will describe the data obtained through direct observation and interviews with the informants in the form of a written report that is supported by various kinds of documents needed in this study. There were five informants in this study. The data analysis technique uses the theory of Miles and Hubberman. The technique of guaranteeing the validity of the data uses triangulation. Based on research findings, the public already understands what Covid-19 is and how it spreads. But there are still people who still don't understand what Covid-19 is and there are also some people who are indifferent to Covid-19 due to economic demands. It is also understandable that currently there are some people who still ignore health protocols because they still don't feel the dangers of Covid-19.